If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -10 = 6x + -1(x + 2) + (-1x + 3) Combine like terms: 15 + -10 = 5 5 = 6x + -1(x + 2) + (-1x + 3) Reorder the terms: 5 = 6x + -1(2 + x) + (-1x + 3) 5 = 6x + (2 * -1 + x * -1) + (-1x + 3) 5 = 6x + (-2 + -1x) + (-1x + 3) Reorder the terms: 5 = 6x + -2 + -1x + (3 + -1x) Remove parenthesis around (3 + -1x) 5 = 6x + -2 + -1x + 3 + -1x Reorder the terms: 5 = -2 + 3 + 6x + -1x + -1x Combine like terms: -2 + 3 = 1 5 = 1 + 6x + -1x + -1x Combine like terms: 6x + -1x = 5x 5 = 1 + 5x + -1x Combine like terms: 5x + -1x = 4x 5 = 1 + 4x Solving 5 = 1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + -4x = 1 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + -4x = 1 + 0 5 + -4x = 1 Add '-5' to each side of the equation. 5 + -5 + -4x = 1 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 1 + -5 -4x = 1 + -5 Combine like terms: 1 + -5 = -4 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| (4x-1)-(x-3)= | | .33a-.75=6 | | (x+2)(x-3)=(x+3)3 | | 3x-2=5(1-9x^2)^1/2 | | 2n+8=-32 | | (3x-11)+(-4+1)= | | 10^5x10^-7/10^2 | | -3x-2x-10=10 | | -9(v+3)=-2v+15 | | a+a+a/3+2=100 | | 6x-(4x+9)=5x-36 | | 6x^2+10xy-4x^2=0 | | 2x^3-7x^2+2x+3=0 | | 234x^2-12x-24=0 | | 4(6y-5)=23-3(8y+1) | | 6x^2+8x-9.5=0 | | -x+16x-2=0 | | 10/40-20x | | y=x*2-4x-12 | | n+2/3=35 | | 48y^3-3u^4y^3=0 | | 9=u/5-9 | | 7h+31-10=35 | | 7-3m=m-8-4m | | 1-0.05z=0.07 | | 3X+8X-4=14+X+7X | | (5x^4+8x)+(x^4+10)= | | 4(3-7x)-(6-3y)=8-2x | | 4/x+3/x=7 | | 4(3-7y)-(6-3x)=8-2y | | 0=4+5 | | x+2/3+x+3/4=5 |